The Law and Politics of Brexit - Volume V: The Trade and Cooperation Agreement - Federico Fabbrini (Oxford University Press, 2024)
The purpose of this book is to offer a comprehensive analysis of the Trade and Cooperation Agreement (TCA), a treaty concluded between the European Union (EU) and the United Kingdom (UK) on Christmas Eve 2020, and which officially entered into force on 1 May 2021. The book builds on a number of earlier volumes on the law and politics of Brexit, but goes beyond them by specifically considering in greater depth those policy areas of EU-UK cooperation which are included in the TCA: ie free movement of goods, customs, rules of origin, services, investment, public procurement, capital movement, intellectual property, transport, aviation, fisheries, health, energy, cyber, and regulatory cooperation, and UK participation in EU programmes. This book, however, does not provide only a technical legal analysis of core provisions of the TCA. Rather, consistent with the ethos of all earlier volumes, it takes an interdisciplinary and policy perspective. On the one hand, it contextualizes the TCA in the political and economic reality in which the treaty operates. On the other hand, it explores the TCA for what it is, but without assuming that this must be the inevitable landing zone of EU-UK cooperation. As such, the book reflects on what the possible prospects to further develop EU-UK relations may be going forward in light of new global, national, and local developments, including the war in Ukraine, a growing public opinion shift against Brexit, and the recent approval of the Windsor Framework defusing EU-UK tensions over Northern Ireland.
Keywords: 340; Brexit; Trade and Cooperation Agreement; Windsor Framework; EU; UK; relationship